Mobile Payment in China: A Study from a Sociological Perspective. (July 2023) - Ye, WeiMing; Chen, Weirong; Fortunati, Leopoldina
This study aims to analyse and clarify why mobile payments have been adopted in China at such a rapid pace. Unlike previous studies which focused on mobile payment functionality and the micro-level reasons for adoption, this study emphasized the macro-level and meso-level reasons with an emphasis on social relationships or guanxi to explain the widespread and rapid adoption in China of mobile payment. Initially mobile payment was widely dispersed by leveraging the trust existing in strong relationship ties (e.g. mobile 'red packets'). In the second phase of mass adoption there was a shift toward relying on economic exchanges in the context of weak urban ties. Now in the third phase mobile payment seeks to abandon social relations altogether relying on technologies for direct human-to-machine interactions. The three successive phases show how the strong interactions between financial regulatory policy and mobile payment development have affected social relationships.